2021
DOI: 10.1111/jog.15014
|View full text |Cite
|
Sign up to set email alerts
|

Survey on spontaneous miscarriage and induced abortion surgery safety at less than 12 weeks of gestation in Japan

Abstract: Aim: In Japan, dilatation and curettage (D&C) is a common procedure for spontaneous miscarriage and induced abortion, and its safety has long been an issue. Electric vacuum aspiration (EVA) is also common, but manual vacuum aspiration (MVA) was introduced recently, with medical abortions using mifepristone or misoprostol which are not yet legally accepted. This nationwide retrospective study surveyed the surgical methods and complications associated with spontaneous miscarriage and induced abortion at less tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The World Health Organization (WHO) includes medical abortion in its Model List of Essential Medicines and recommends avoiding curettage, 3 which is used for one-fourth of early abortions in Japan. 4 The Phase III study of medical abortion pills in Japan reported a high success rate (93.3%) and a low frequency of bleeding as a severe complication (0.8%). 5 In addition, a study in the Netherlands reported a higher satisfaction (answering “very much”) among women choosing medical abortion (45%) compared to vacuum aspiration (31%).…”
mentioning
confidence: 99%
“…The World Health Organization (WHO) includes medical abortion in its Model List of Essential Medicines and recommends avoiding curettage, 3 which is used for one-fourth of early abortions in Japan. 4 The Phase III study of medical abortion pills in Japan reported a high success rate (93.3%) and a low frequency of bleeding as a severe complication (0.8%). 5 In addition, a study in the Netherlands reported a higher satisfaction (answering “very much”) among women choosing medical abortion (45%) compared to vacuum aspiration (31%).…”
mentioning
confidence: 99%
“…Indeed, in 2015, a Japanese nationwide survey reported that D&C resulted in higher risk of uterine perforation compared to VA (36.4/100 000 vs. 4.9/10 0000, P = 0.047) 11 . However, in 2019, 23.5% of induced abortions were still performed by D&C, 40.3% by VA with curettage, and only 36% by VA only 12 …”
mentioning
confidence: 99%
“…11 However, in 2019, 23.5% of induced abortions were still performed by D&C, 40.3% by VA with curettage, and only 36% by VA only. 12 Obstetricians and gynecologists should provide sexual and reproductive health and rights services, including safe abortion care, based on scientific evidence within the framework of rights. JSOG's strong leadership is expected.…”
mentioning
confidence: 99%